The proposed U. P. stub line rail road - Haynes, Benjamin T. Jr. (My University, 1902)
Introduction: As a student of the Kansas State Agricultural College I have been between her walls for the past four years laboring to complete one of her courses and incidentally watching the growth of the institution. During this time many changes have necessarily taken place; especially in the line of improvement of her building accommodations. This period of time has seen her repair the old barn, lots, library building, chemical laboratory; build a new cow barn, silo, agricultural hall, physical science hall, and many minor improvements. Still she is in need of many other buildings such as a new chapel, a president’s mansion, a veterinary science building, all of which must come about by state appropriations—those needed most will probably be supplied firs and will come no sooner than the college demand them. Another present need of the college and one I believe necessary and highly beneficial is that of a switch or stub line railroad from the depot to the college; so I have taken it upon myself to survey and establish a grade line from the Union Pacific depot to the college shops.
Citation: Haynes, Benjamin T. Jr. The proposed U. P. stub line rail road. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Kansas State Agricultural College; Union Pacific Railroad; Stub Line Railroad; Theses; Manuscripts (documents)